Assisting Teachers in Developing Qirā’ah Learning Materials Based on Message Design Principles - Hamdy, Mohammad; Nasrullah, Nasrullah; Muhammad, Jiddah Hassan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The teaching of Qirā’ah (Arabic reading comprehension) at STAI Darul Ulum Banyuanyar Pamekasan has long faced challenges due to the use of monotonous and text-heavy learning materials. The existing textbooks consist mainly of reading passages and simple exercises that fail to attract students’ interest or encourage autonomous learning beyond the classroom. This community service project aimed to assist Arabic language teachers in developing Qirā’ah learning materials based on message design principles, emphasizing clarity, visual appeal, and pedagogical effectiveness. A participatory mentoring approach was employed, involving workshops, collaborative material design, and expert validation led by Dr. Jiddah Hassan Muhammad from the University of Maiduguri, Nigeria. Data were collected through observation, documentation, and focus group discussions, and analyzed qualitatively using Miles and Huberman’s interactive model. The findings revealed significant improvement in teachers’ ability to integrate design elements and semiotic principles—particularly Peirce’s triadic model of icon, index, and symbol—into their instructional materials. The newly developed Qirā’ah resources showed increased visual coherence and motivational value, resulting in greater student engagement and comprehension. The mentoring process also fostered cross-cultural academic collaboration, enhancing pedagogical insight and professional competence among participating teachers. This project contributes to Arabic education by demonstrating how message design theory and semiotics can be effectively applied to religious and linguistic learning contexts, bridging the gap between traditional textual instruction and modern educational design